Punk Episode 1-4 - Miller, Jesse James; Lawless, Shaun (Dazzler Media, 2020)
"Punk" is a 4-part series exploring the history of punk music featuring global music icons. Interspersing stories from America's punk pioneers with those of UK bands of the same ilk looking to conquer the USA, Punk defines the genre's American DNA and explores its subsequent propagation across the Atlantic. Featuring a seamless blend of rare and unseen photos and gritty video, a crackling soundtrack of punk hits and misses, original interviews and VIP access to the scene s biggest movers and shakers including to name just a few. From the ink-stained fingers that produced Xeroxed fanzines, to the kids packing basements and warehouse spaces, to hundreds of bodies slamming into one another and rushing makeshift stages, "Punk" reveals for the first time the profound effect America had on this global popular culture. [www.amazon.co.uk]
Keywords: Blu-Ray-Disc